(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2015)
A total of 39 Fusarium graminearum, F. sporotrichioides, F. semitectum and F. equiseti isolates, originating from wheat and maize samples collected at 10 locations in Serbia, were analyzed by ELISA method for their potential of deoxynivalenol (DON) and zearalenone (ZEA) production under optimal laboratory conditions. Fusarium graminearum isolates with the highest intraspecies variability were the best producers of both deoxynivalenol and zearalenone. In contrast, F. equiseti isolates were the weakest producers of these two toxins. Considering the plant origin of the isolates, wheat-originating F. sporotrichioides isolates were better deoxynivalenol producers, while the maize-originating isolates produced more zearalenone. There was no clear difference in ZEA production between wheat- and maize-originating isolates of F. graminearum, while higher average DON concentrations were produced by F. graminearum wheat-originating isolates. Negative correlation was detected between the production of deoxynivalenol and zearalenone by various Fusarium spp.